The effect of using a measuring instrument to analyse the level of creative thinking of visual arts students from a teaching perspective - Bouwer, Willem Christiaan (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPhil)--Stellenbosch University, 2022.